Study on the Synchronistic King List from Ashur - Chen, Fei, (Cuneiform Monographs ;, 2020)
In Study on the Synchronistic King List from Ashur, CHEN Fei conducts a full investigation into that king list, which records all the kings of Assyria and Babylonia in contemporary pairs from the 18th to the 7th century BC. The texts of all the exemplars of the Synchronistic King List are reconstructed anew by the existing studies and the author's personal collations on their sources, and part of the text of the main exemplar is thus revised. The author also looks into the format of the Synchronistic King List and draws the conclusion that the Synchronistic King List was composed by Ashurbanipal, king of Assyria, to support his Babylonian policy.